VIOLENT BEHAVIOURAL PATTERNS IN THE REALITY SHOW "COUPLES" - Terek, Lidija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
The paper is dealing with the problem of violent behaviour in the reality show "Couples" (Parovi), which is broadcasted on Happy TV, a commercial television with a national frequency in Serbia. Based on the idea that the conditions in reality shows are conducive to violence due to a large amount of character interaction and little plot, and guided by the results of the research that studied violent behaviours in reality shows in the UK, our research aimed to determine which forms of violent behaviour are most prevalent in this reality show, in what situations and under what circumstances violent behaviours mostly occur, as well as who commits violence most often. The results showed that the most common forms of violence were direct emotional/psychological violence, that the most frequent and diverse violent behaviour was expressed by the Production and TV hosts, that nearly all the violent behaviour of participants were a reaction to the Production‘s and hosts’ provocation and manipulation, as well as that individuals, who have a history of violent behaviour, most often behaved violently during the show. The obtained results proved that the Production of this reality show intends to provoke conflicts and violent behaviours, to compensate for the lack of story.